(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
The aims of this article is to presente some preventive conservation actions for the embroidery, that is part of the vestments of Brazilian sacred statuary. Through an exploratory investigation, it was verified that there weren’t bibliographies about this topic. Hence the need to contribute to this theme, using as a reference two studies that involved the conservation of embroidery in stones. One of which was carried out on a dress from the 70s, that is a part of Brazilian cultural history and another, referring to a old embroidery made on paper, from a region of Portugal. Both studies showed stages of embroidery conservation, being relevant as an example of actions that can be applied to the preservation of embroidery on Brazilian sacred statuary garments. As a final consideration, it is recomended that more studies be carried out about this topic, that is so important and still so devoid of bibliographies.